(untitled) (International journal of artificial intelligence, 2024)
The theory of speech acts, which, due to its methodological status, has become a separate field of anthropocentric theory, is a phenomenon formed on the basis of a philosophical view of language, the main essence of which is associated with speech phenomena. Issues of the theory of speech acts are essentially at the center of a number of areas of linguistics, such as the relatively new “Psycholinguistics, pragmalinguistics, sociolinguistics, ethnolinguistics, communicative syntax, rhetoric, semiotics”. One of the promising areas of speech research is linguistic pragmatics, which studies speech activity in terms of the point of determining the correlation between the use of language units and the goals of speakers.